The Stabilizing Effect of the ERMon Exchange Rates and Interest Rates : An Empirical Investigation - Artis, Michael (IMF Working Papers; Working Paper, 1993)
This paper applies nonparametric test procedures to test for a shift in the volatility of nominal and real exchange rates for ERM members and nonmembers. The results imply a reduction in volatility for the ERM members, especially during the second half of the period of operation of the ERM. We also demonstrate that this enhanced stability was not bought at the expense of increased interest rate volatility. The issue of interest rate volatility during sterling's participation in the ERM is also examined.